Evidence-based treatment of pyelonephritis and other urinary tract infections - Drekonja, Dimitri (Henry Stewart Talks, 2023)
Epidemiology of urinary tract infections (UTI), Cystitis, Pyelonephritis, Febrile UTI, Urosepsis, Emphysematous pyelonephritis, Bacteriuria/pyuria of clinically undetermined significance (BPCUS), Asymptomatic bacteriuria, Prostatitis, ‘Complicated’ UTIs